CLINICAL ADVANTAGES OF TELMISARTAN: FEATURES OF PHARMACOKINETICS, PHARMACODYNAMICS AND EFFECTS ON THE DAILY BLOOD PRESSURE PROFILE - O. D. Ostroumova; E. A. Smolyarchuk; O. V. Bondarec; E. E. Paleeva (Столичная издательская компания, 2017)
The features of the pharmacokinetics of the angiotensin II receptor blocker telmisartan are considered. Thanks to these features it has a number of advantages in comparison with other angiotensin II receptor blockers and antihypertensive drugs from other classes. Particular attention is paid to the long half-life of telmisartan, which retains its effect for more than 24 hours. This is especially important for controlling blood pressure (BP) in the early morning hours. Data from studies demonstrating that excessive BP rises in the early morning hours increase the risk of cardiovascular and cerebrovascular complications are presented. The results of comparative studies of telmisartan using the ambulatory BP monitoring, which testify to its advantages in BP control within 24-hours, are considered.